2016
DOI: 10.1080/10245332.2016.1147678
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vaccinia-related kinase 1 (VRK1) accelerates cell proliferation but overcomes cell adhesion mediated drug resistance (CAM-DR) in multiple myeloma

Abstract: Our data supports a role for VRK1 in MM cell proliferation, adhesion, and drug resistance, and it may pave the way for a novel therapeutic approach for CAM-DR in MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the present study, it was also found that VRK1 expression was highest in both NCI-H520 and SK-MES-1 cell lines, and the cell viability of NCI-H520 and SK-MES-1 in the shVRK1 group was signifcantly lower than that in the shNC group, and SK-MES-1 in the shVRK1 group had signifcantly lower cell viability than in the shNC group. Previously, it was shown that VRK1 expression could promote cell proliferation in myeloma by regulating cell cycle-related proteins [18]. Te current study found that the inhibition of LUSC cell proliferation was due to depletion of VRK1, which induces the cell cycle arrest in the G0/G1 phase, which is also consistent with Carrion-Marchante et al [19].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, it was also found that VRK1 expression was highest in both NCI-H520 and SK-MES-1 cell lines, and the cell viability of NCI-H520 and SK-MES-1 in the shVRK1 group was signifcantly lower than that in the shNC group, and SK-MES-1 in the shVRK1 group had signifcantly lower cell viability than in the shNC group. Previously, it was shown that VRK1 expression could promote cell proliferation in myeloma by regulating cell cycle-related proteins [18]. Te current study found that the inhibition of LUSC cell proliferation was due to depletion of VRK1, which induces the cell cycle arrest in the G0/G1 phase, which is also consistent with Carrion-Marchante et al [19].…”
Section: Discussionsupporting
confidence: 90%
“…Our gene expression and ontology analysis predicts that VRK1 expression is associated in neuroblastoma tumors with signaling pathways involved in cell cycle regulation, DNA replication or DNA repair. VRK1 has been described as a proliferation control protein in human fibroblasts and in some cancers like head and neck or myeloma [19,29,30]. We have identified that VRK1 is associated with cell proliferation in NB tumor cells and that it is an essential gene controlling cell division in these tumors.…”
Section: Discussionmentioning
confidence: 84%
“…The VRK1 protein has characteristics that make it distinct and candidate for development of highly specific inhibitors [ 13 ], one of which has been recently developed [ 15 , 16 ]. VRK1 has been associated with the control of cell proliferation [ 17 ] and mitosis [ 18 , 19 ], and is expressed at high levels in proliferating and tumor cells [ 17 , 20 ], which is an indicator of a poorer prognosis in many tumor types [ 21 25 ]. VRK1 is also necessary to maintain genomic stability and its loss facilitates DNA damage by a defective DNA damage response [ 20 , 26 ].…”
Section: Introductionmentioning
confidence: 99%